High-oxygen-index and low-acid-precipitation red phosphorus flame-retardant polyamide composite material and preparation method thereof
The red phosphorus flame retardant masterbatch was prepared through different coating methods and the flame retardant synergist and acid respirator were added, which solved the problems of low oxygen index and acid precipitation of red phosphorus flame retardant polyamide materials, achieved the combination of high oxygen index and low acid precipitation performance, and met the fire resistance requirements of high-end products.
Patent Information
- Application Number
- CN202411894457.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-15
AI Technical Summary
The existing red phosphorus flame-retardant polyamide materials have a low oxygen index, which is difficult to meet the fire protection requirements of high-end electronic appliances and rail transit vehicles. At the same time, the materials are prone to acid precipitation problems during long-term use, resulting in poor power supply for the product or fire.
Red phosphorus flame retardant masterbatches are prepared by different coating methods, and an appropriate amount of flame retardant synergist and acid respirator are added to improve the oxygen index of the material and inhibit acid precipitation. Specifically, it includes homemade magnesium hydroxide, silica, diethyl aluminum hypophosphate/silica, melamine cyanurate/silica and other coatings using polyamide 6 as a carrier, combining synergistic agents such as zinc borate and nano zinc oxide and acid absorbents such as copper oxide and calcium oxide.
It significantly improves the oxygen index of the material, meets the HL3 level requirements in the fire protection EN 45545-2 standard for rail transit vehicles, and effectively inhibits the acid precipitation problem and reduces the acid precipitation risk of the material.
Abstract
Description
Technical Field
[0001] The invention relates to the field of modified polymer new materials, and in particular to a high oxygen index, low acid precipitation red phosphorus flame retardant polyamide composite material and a preparation method thereof. Background Art
[0002] The unique polar amide groups on the main chain of polyamide materials make it easy to form hydrogen bonds between molecules, and the flexible molecular chain structure makes it easy to crystallize. The formation of hydrogen bonds and high crystallinity give polyamide materials high wear resistance, melting point and mechanical properties. At the same time, due to good electrical properties, heat resistance, oil resistance, elasticity, biocompatibility and molding processability, polyamide materials are widely used in machinery, automobiles, electrical appliances, textile equipment, aviation, metallurgy, medical and other fields.
[0003] Due to the high H / C content ratio of polyamide materials, polyamide 6 and polyamide 66 have low limiting oxygen index. When used in the electrical or automotive industry, they are prone to fires due to extreme situations such as leakage and electric sparks, which seriously limits their application in related fields. Therefore, polyamide materials need to be modified in terms of flame retardancy to meet market demand. Red phosphorus masterbatch flame retardant is an inorganic halogen-free flame retardant with excellent thermal stability, high flame retardant efficiency, good electrical insulation, and low addition amount. It has always attracted widespread attention in the industry.
[0004] The oxygen index of red phosphorus flame retardant polyamide materials is about 28%, which cannot meet the use requirements of some high-end electronic appliances and the automotive industry. In particular, with the promulgation of the EN 45545-2 standard for fire protection of rail transit vehicles, higher requirements are placed on the oxygen index of polyamide flame retardant materials. At the same time, red phosphorus flame retardant polyamide materials are prone to acid precipitation during long-term use, resulting in a sharp increase in product contact resistance, poor product power supply, and even fire, causing significant losses to people's property and lives. Therefore, the development of high oxygen index and low acid precipitation red phosphorus flame retardant materials has become a development trend in the future modification industry.
[0005] Patent CN 108997742A (application number 201810959366.X) uses a compatibilizer to add a high oxygen index polyamide resin to a low oxygen index polypropylene resin for alloy blending, which not only improves the oxygen index of the alloy material and reduces the smoke density of the alloy material, but also does not require the addition of flame retardants during the preparation process, which helps to improve the processing and forming properties of the alloy material. However, the oxygen index of this solution is limited (from 22.5% to 23.5%) and cannot meet the high requirements of high-end products.
[0006] Patent CN13602061B (application number 201310532534.4) adds 3-8% of halogen-free flame retardant synergist (MCA and OMMT are blended in a certain proportion), which better exerts the compounding effect of red phosphorus flame retardant and halogen-free flame retardant synergist, so that the oxygen index of red phosphorus flame retardant reinforced nylon 66 material is increased to more than 28%. Since the amount of added halogen-free flame retardant synergist is small, the mechanical properties of the material are less affected. While the oxygen index of the flame retardant material is improved, the mechanical properties and other properties can be maintained well, which better meets the use requirements of red phosphorus flame retardant reinforced nylon 66 in the fields of electronics and electrical appliances that require an oxygen index of more than 28%. However, the oxygen index of the patent only meets the requirements of HL2 for R22 products in the EN 45545-2 standard for fire protection of rail transit vehicles, and cannot meet the higher HL3 level requirements, and no solution is given to the acid precipitation problem that is prone to occur in red phosphorus flame retardant polyamide materials.
[0007] Due to the low oxygen index of polyamide resin, the oxygen index of red phosphorus flame retardant nylon material must reach 32%, which is very difficult to meet the HL3 level in the rail transit vehicle fire protection standard EN 45545-2. In addition, red phosphorus flame retardant nylon material is prone to acid precipitation after long-term use. It is technically difficult to simultaneously ensure the high oxygen index and low acid precipitation performance of red phosphorus flame retardant nylon material. Summary of the invention
[0008] The present invention provides a red phosphorus flame retardant polyamide composite material with a high oxygen index and low acid precipitation. A variety of coated red phosphorus flame retardant masterbatches are prepared by using different red phosphorus coating methods, and then a suitable flame retardant synergist and an acid absorber are added to improve the oxygen index of the material while inhibiting the acid precipitation of the material. The composite material can be widely used in the fields of electrical appliances, automobiles, aviation, medical treatment, rail transit, etc.
[0009] A high oxygen index, low acid precipitation red phosphorus flame retardant polyamide composite material, comprising the following components by weight percentage: Polyamide 30%-60%, filling component 10%-40%, coated red phosphorus flame retardant masterbatch 5%-20%, flame retardant synergist 1%-10%, acid absorber 0.1%-1%, lubricant 0.1%-1% and antioxidant 0.1%-1%.
[0010] The polyamide is at least one of polyamide 6, polyamide 66 or polyamide 56. Preferably, the relative viscosity of the polyamide 6 is 2.45, the relative viscosity of the polyamide 66 is 2.7, and the relative viscosity of the polyamide 56 is 2.5. The viscosity of polyamide 6, polyamide 66 and polyamide 56 can ensure that the mixture has good melt strength during the twin-screw extrusion process, which is conducive to the uniform dispersion of the coated red phosphorus flame retardant masterbatch, filling components, flame retardant synergists, acid absorbers and other additives in the screw, thereby improving the production stability.
[0011] The filling component is at least one of alkali-free glass fiber, carbon fiber, talcum powder, calcium carbonate, wollastonite, glass microbeads and silicon dioxide.
[0012] Preferably, the filling component is alkali-free glass fiber, and the diameter of the glass fiber is 7-10 μm.
[0013] The coated red phosphorus flame retardant masterbatch is at least one of a self-made magnesium hydroxide coated red phosphorus flame retardant masterbatch, a silicon dioxide coated red phosphorus flame retardant masterbatch, a diethyl aluminum hypophosphite / silicon dioxide coated red phosphorus flame retardant masterbatch, and a melamine cyanurate / silicon dioxide coated red phosphorus flame retardant masterbatch using polyamide 6 as a carrier.
[0014] The method for preparing the homemade magnesium hydroxide coated red phosphorus flame retardant masterbatch comprises the following steps: Step 1: Add 200 g of magnesium sulfate heptahydrate into 600 mL of deionized water, and after the system temperature rises to 70° C., stir at a stirring speed of 300 r / min until the magnesium sulfate heptahydrate is completely dissolved.
[0015] Step 2: add 100g red phosphorus (particle size 50μm) and 10g sodium dodecylbenzene sulfonate dispersant, stir for 5min, add 5% sodium hydroxide solution to adjust the pH to 10, add 1g 5% aluminum sulfate aqueous solution, react at 75°C for 2h, and after the reaction, vacuum filter, wash the filter cake 3 times with deionized water, and then dry at 120°C for 10h to obtain magnesium hydroxide-coated red phosphorus.
[0016] Step 3: After the magnesium hydroxide coated red phosphorus is dried, it is granulated with polyamide 6 in a certain proportion through a twin-screw extruder to obtain magnesium hydroxide coated red phosphorus flame retardant masterbatch.
[0017] The method for preparing the homemade silicon dioxide-coated red phosphorus flame retardant masterbatch comprises the following steps: Step 1: Add 100 g red phosphorus (particle size 50 μm), 220 mL 25% ammonia water and 400 mL tetraethyl orthosilicate into 5 L ethanol, stir at 40 °C for 20 min, and ultrasonicate for 15 min; Step 2: Take 1L of ethanol / water mixture, slowly add it into the reaction system with a microfluidic injection pump, continue stirring and reacting for 6 hours, centrifuge, and vacuum dry at 120°C for 10 hours to obtain silica-coated red phosphorus; Step 3: After the silica-coated red phosphorus is dried, it is granulated with polyamide 6 in a certain ratio through a twin-screw extruder to obtain the silica-coated red phosphorus flame retardant masterbatch.
[0018] The method for preparing the self-made diethyl aluminum hypophosphite / silicon dioxide coated red phosphorus flame retardant masterbatch comprises the following steps: Step 1: Add 100 g of silica-coated red phosphorus into 150 mL of deionized water, then add 0.5 g of diethylaluminum hypophosphite (Clariant OP1230), and start stirring; Step 2: Adjust the pH value of the solution to 4 with 5% sulfuric acid solution, raise the temperature to 55°C, and then adjust the pH value to neutral with 5% sodium hydroxide solution, keep warm at 55°C for 60 min, cool to room temperature, vacuum filter, wash the filter cake with water, transfer to a vacuum oven and dry at 100°C for 3h to obtain diethyl aluminum hypophosphite / silicon dioxide organic-inorganic double-layer coated red phosphorus.
[0019] Step 3: After the diethyl aluminum hypophosphite / silicon dioxide coated red phosphorus is dried, it is granulated with polyamide 6 in a certain ratio through a twin-screw extruder to obtain the diethyl aluminum hypophosphite / silicon dioxide organic-inorganic coated red phosphorus masterbatch.
[0020] The preparation method of the melamine cyanurate / silicon dioxide coated red phosphorus masterbatch comprises the following steps: Step 1: add 100 g of silica-coated red phosphorus to 1 L of deionized water, then add 10 g of melamine and 10 g of cyanuric acid, heat to 95° C., stir and react for 1 h, centrifuge, and vacuum dry to obtain melamine cyanurate / silicon dioxide organic-inorganic double-layer coated red phosphorus; Step 2: After the melamine cyanurate / silicon dioxide coated red phosphorus is dried, it is granulated with polyamide 6 in a certain proportion through a twin-screw extruder to obtain a melamine cyanurate / silicon dioxide organic-inorganic coated red phosphorus masterbatch.
[0021] The red phosphorus content of the self-made magnesium hydroxide coated red phosphorus flame retardant masterbatch, the silicon dioxide coated red phosphorus flame retardant masterbatch, the diethyl aluminum hypophosphite / silicon dioxide coated red phosphorus masterbatch, and the melamine cyanurate / silicon dioxide coated red phosphorus masterbatch is 40%.
[0022] The synergistic flame retardant is at least one of zinc borate, zinc stannate, barium metaborate, nano zinc oxide and nano aluminum hydroxide.
[0023] The acid absorbent is at least one of copper oxide, calcium oxide, lanthanum oxide, cerium oxide and organic nano-montmorillonite.
[0024] Preferably, the acid absorbent is a mixture of calcium oxide and nano-montmorillonite in a weight ratio of (1:2) to (3:1).
[0025] The lubricant is at least one of TAF, EBS, TPP, sebacic acid, silicone, montan wax or mesic acid amide.
[0026] The antioxidant is at least one of 1010, 168, 1098, 9228, 1076, DLTP and SEED.
[0027] The method for preparing the high oxygen index and low acid precipitation red phosphorus flame retardant polyamide composite material comprises the following steps: The polyamide, the filling component, the coated red phosphorus flame retardant masterbatch, the synergistic flame retardant, the acid absorber, the lubricant and the antioxidant are extruded from a twin-screw extruder, and after cooling, drying and pelletizing, a high oxygen index and low acid precipitation red phosphorus flame retardant polyamide composite is obtained.
[0028] The polyamide resin, synergistic flame retardant, acid absorber, lubricant and antioxidant are uniformly stirred and added from the No. 1 discharge port of the twin-screw extruder; the filling component is added from the No. 2 discharge port of the twin-screw extruder; and the coated red phosphorus flame retardant masterbatch is added from the No. 3 discharge port of the twin-screw extruder.
[0029] The process temperatures of the twin-screw extruder from the first feeding section to the die head are: 240℃-280℃, 250℃-290℃, 250℃-290℃, 240℃-290℃, 230℃-280℃, 220℃-280℃, 210℃-270℃, 200℃-270℃, 200℃-270℃, 230℃-290℃ Compared with the prior art, the present invention has the following advantages: The present invention uses a variety of coating methods to coat red phosphorus, which can reduce the amount of oxygen-containing acids generated by phosphoric acid, phosphorous acid, hypophosphorous acid and other phosphorus during long-term use of the material, and improve the acid precipitation resistance of the material. At the same time, the addition of an acid absorber can further reduce the risk of acid precipitation of the material. The homemade melamine cyanurate / silicon dioxide coated red phosphorus masterbatch coating layer of the present invention can also form an efficient phosphorus, silicon, and nitrogen synergistic flame retardant system with red phosphorus, and work together with the synergistic flame retardant to greatly improve the oxygen index of the material. The present invention has broad application potential in the fields of electronics, aerospace, automobile industry, rail transportation, and medical treatment. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods.
[0031] The raw material formulas of the following Examples 1 to 8 and Comparative Examples 1 to 4 are listed in Table 1 below by weight percentage, and all adopt the following preparation process: Weigh the raw materials according to the mass percentage content. First, dry the polyamide resin and the coated red phosphorus flame retardant masterbatch. After drying, mix the polyamide resin, flame retardant synergist, acid absorber, lubricant and antioxidant evenly and add them to the No. 1 feeding hopper of the twin-screw extruder. The filling component is added from the No. 2 feeding hopper of the twin-screw extruder, and the coated red phosphorus flame retardant masterbatch is added from the No. 3 feeding hopper of the twin-screw extruder. After melting, blending, extrusion, cooling, air drying and granulation, a high oxygen index and low acid precipitation red phosphorus flame retardant polyamide composite material is obtained; wherein, the extrusion processing temperature is 220-280°C, and the screw speed is 300-350 rpm.
[0032] Performance characterization and test methods: The composite materials prepared in the above comparative examples and embodiments are measured by simply supported beam notched impact strength with reference to GB / T1043.1-2008 standard using a simply supported beam impact tester; vertical combustion flame retardancy is measured with reference to GB / T 2408-2008 standard using a vertical-horizontal combustion measuring instrument; oxygen index test is measured with reference to GB / T 2406.2-2009 standard; acid precipitation total phosphorus test requires pretreatment of the sample strips, the treatment method is: cut 5g sample strips into pieces, add 30mL deionized water, heat at 100℃ for 4h, and take the supernatant for testing. The test method is measured with reference to GB / T 11893-1989 standard using an ultraviolet visible spectrophotometer.
[0033] The performance test results of the materials obtained from the embodiments and comparative examples in Table 1 are shown in Table 2.
[0034] Components Remark Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Nylon resin PA66 Huayang 1800 54 54 54 54 54 53 53.5 53 57.5 54.5 54 54 Alkali-free chopped glass fiber Jushi Group, Model 988A 30 30 30 30 30 30 30 30 30 30 30 30 FR4140R Tongcheng Xinde New Materials 12 12 12 12 Magnesium hydroxide coated red phosphorus masterbatch self made 12 Silica coated red phosphorus masterbatch self made 12 Diethyl aluminum hypophosphite / silicon dioxide coated red phosphorus masterbatch self made 12 Melamine cyanurate / silicon dioxide coated red phosphorus masterbatch self made 12 12 12 12 12 Barium metaborate Shandong Xinghai Chemical 3 3 3 3 Anhydrous zinc borate Jinan Taixing Chemical 3 3 3 3 3 3 3 Nano-montmorillonite Zhejiang Huate New Materials 1 0.5 0.5 0.5 Calcium Oxide Jinan Yueyang Chemical 0.5 0.5 0.5 0.5 0.5 0.5 0.5 1 0.5 Lubricant TAF Suzhou Xingtai Guoguang 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 Antioxidant 1098 BASF 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Antioxidant 9228 BASF 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1
[0035] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 <![CDATA[Notched impact strength (KJ / m 2 ).]]> 7.9 7.7 8.4 8.2 7.8 7.1 7.5 7.4 7.8 7.5 6.3 6.9 Vertical burning (1.6mm) V-0 V-0 V-0 V-0 V-0 V-0 V-0 V-0 V-1 V-0 V-0 V-0 Oxygen index (%) 29.4 29.8 31.5 32.3 33.5 34.4 34.7 33.9 26.5 27.9 28.1 27.8 Total phosphorus (mg / L) 2.2 2.4 1.3 1.1 1.2 1.0 0.4 1.1 8.2 8.3 7.3 7.1 By comparing Examples 1-4 and Comparative Example 4, it can be found that the oxygen index of the self-made coated red phosphorus flame retardant masterbatch material is significantly improved and the total phosphorus value is significantly reduced compared with the commercially available FR4140R red phosphorus masterbatch material. In particular, the material prepared by using melamine cyanurate / silicon dioxide coated red phosphorus masterbatch has an oxygen index increased from 27.8% to 32.3%, and the total phosphorus value has decreased from 7.1 mg / L to 1.1 mg / L. The oxygen index has met the highest grade requirement (HL3) for rail transit R22 category materials. By comparing Examples 4-5 and Comparative Example 1, it can be found that anhydrous zinc borate and barium metaborate synergistic red phosphorus can both increase the oxygen index of the material, and the improvement effect of barium metaborate is better. By comparing Examples 6-8, it can be found that when the acid absorber calcium oxide and nano-montmorillonite are added in a ratio of 1:1, the total phosphorus of the material is the smallest and the risk of acid precipitation is the lowest.
[0036] The present invention and its implementation methods are described above, and the above description is not restrictive, and the actual structure is not limited thereto. If a person skilled in the art is inspired by it and designs a structural method and an implementation method similar to the technical solution without innovating without departing from the main purpose of the invention, they shall all fall within the protection scope of the present invention.
Claims
1. A high oxygen index, low acid precipitation red phosphorus flame retardant polyamide composite material, comprising the following components: In terms of weight percentage, the raw material composition includes: Polyamide 30%-60%, filling component 10%-40%, coated red phosphorus flame retardant masterbatch 5%-20%, flame retardant synergist 1%-10%, acid absorber 0.1%-1%, lubricant 0.1%-1% and antioxidant 0.1%-1%.
2. A high oxygen index, low acid precipitation red phosphorus flame retardant polyamide composite material as claimed in claim 1, characterized in that: The polyamide is at least one of polyamide 6, polyamide 66 or polyamide 56; The filling component is at least one of alkali-free glass fiber, carbon fiber, talcum powder, calcium carbonate, wollastonite, glass microbeads, and silicon dioxide; The lubricant is at least one of TAF, EBS, TPP, sebacic acid, silicone, montan wax or mesic acid amide; The antioxidant is at least one of 1010, 168, 1098, 9228, 1076, DLTP and SEED; The synergistic flame retardant is at least one of zinc borate, zinc stannate, barium metaborate, nano zinc oxide and nano aluminum hydroxide.
3. A high oxygen index, low acid precipitation red phosphorus flame retardant polyamide composite material as claimed in claim 1, characterized in that: The coated red phosphorus flame retardant masterbatch is at least one of a self-made magnesium hydroxide coated red phosphorus flame retardant masterbatch, a silicon dioxide coated red phosphorus flame retardant masterbatch, a diethyl aluminum hypophosphite / silicon dioxide coated red phosphorus masterbatch, and a melamine cyanurate / silicon dioxide coated red phosphorus masterbatch using polyamide 6 as a carrier.
4. A high oxygen index, low acid precipitation red phosphorus flame retardant polyamide composite material as claimed in claim 3, characterized in that: The method for preparing the homemade magnesium hydroxide coated red phosphorus flame retardant masterbatch comprises the following steps: Step 1: Add 200 g of magnesium sulfate heptahydrate into 600 mL of deionized water, and stir at a stirring speed of 300 r / min until the magnesium sulfate heptahydrate is completely dissolved after the system temperature rises to 70°C; Step 2: add 100g red phosphorus (particle size 50μm) and 10g sodium dodecylbenzene sulfonate dispersant, stir for 5min, add 5% sodium hydroxide solution to adjust the pH to 10, add 1g 5% aluminum sulfate aqueous solution, react at 75°C for 2h, after the reaction, vacuum filter, wash the filter cake with deionized water 3 times, and then dry at 120°C for 10h to obtain magnesium hydroxide-coated red phosphorus; Step 3: After the magnesium hydroxide-coated red phosphorus is dried, the magnesium hydroxide-coated red phosphorus is granulated with polyamide 6 in a certain proportion through a twin-screw extruder to obtain a magnesium hydroxide-coated red phosphorus flame retardant masterbatch.
5. The high oxygen index, low acid precipitation red phosphorus flame retardant polyamide composite material according to claim 3, characterized in that: The method for preparing the homemade silicon dioxide-coated red phosphorus flame retardant masterbatch comprises the following steps: Step 1: Add 100 g red phosphorus (particle size 50 μm), 220 mL 25% ammonia water and 400 mL tetraethyl orthosilicate into 5 L ethanol, stir at 40 °C for 20 min, and ultrasonicate for 15 min; Step 2: Take 1L of ethanol / water mixture, slowly add it into the reaction system with a microfluidic injection pump, continue stirring and reacting for 6 hours, centrifuge, and vacuum dry at 120°C for 10 hours to obtain silica-coated red phosphorus; Step 3: After the silica-coated red phosphorus is dried, it is granulated with polyamide 6 in a certain ratio through a twin-screw extruder to obtain the silica-coated red phosphorus flame retardant masterbatch.
6. The high oxygen index, low acid precipitation red phosphorus flame retardant polyamide composite material according to claim 3, characterized in that: The method for preparing the self-made diethyl aluminum hypophosphite / silicon dioxide coated red phosphorus flame retardant masterbatch comprises the following steps: Step 1: Add 100 g of silica-coated red phosphorus into 150 mL of deionized water, then add 0.5 g of diethylaluminum hypophosphite (Clariant OP1230), and start stirring; Step 2: adjust the solution pH to 4 with 5% sulfuric acid solution, heat to 55°C, and then adjust the pH to neutral with 5% sodium hydroxide solution, keep at 55°C for 60 min, cool to room temperature, vacuum filter, wash the filter cake with water, transfer to a vacuum oven and dry at 100°C for 3h to obtain diethyl aluminum hypophosphite / silicon dioxide organic-inorganic double-layer coated red phosphorus; Step 3: After the diethyl aluminum hypophosphite / silicon dioxide coated red phosphorus is dried, it is granulated with polyamide 6 in a certain ratio through a twin-screw extruder to obtain the diethyl aluminum hypophosphite / silicon dioxide organic-inorganic coated red phosphorus masterbatch.
7. A high oxygen index, low acid precipitation red phosphorus flame retardant polyamide composite material as claimed in claim 3, characterized in that: The method for preparing the homemade melamine cyanurate / silicon dioxide coated red phosphorus masterbatch comprises the following steps: Step 1: add 100 g of silica-coated red phosphorus to 1 L of deionized water, then add 10 g of melamine and 10 g of cyanuric acid, heat to 95° C., stir and react for 1 h, centrifuge, and vacuum dry to obtain melamine cyanurate / silicon dioxide organic-inorganic double-layer coated red phosphorus; Step 2: After the melamine cyanurate / silicon dioxide coated red phosphorus is dried, it is granulated with polyamide 6 in a certain proportion through a twin-screw extruder to obtain a melamine cyanurate / silicon dioxide organic-inorganic coated red phosphorus masterbatch.
8. The high oxygen index, low acid precipitation red phosphorus flame retardant polyamide composite material according to claim 3, characterized in that: The red phosphorus content of the self-made magnesium hydroxide coated red phosphorus flame retardant masterbatch, the silicon dioxide coated red phosphorus flame retardant masterbatch, the diethyl aluminum hypophosphite / silicon dioxide coated red phosphorus masterbatch, and the melamine cyanurate / silicon dioxide coated red phosphorus masterbatch is 40%.
9. The high oxygen index, low acid precipitation red phosphorus flame retardant polyamide composite material according to claim 1, characterized in that: The acid absorbent is at least one of copper oxide, calcium oxide, lanthanum oxide, cerium oxide and nano-montmorillonite.
10. A method for preparing a high oxygen index, low acid precipitation red phosphorus flame retardant polyamide composite material according to claims 1-9, comprising the following steps: The polyamide, the filling component, the coated red phosphorus flame retardant masterbatch, the synergistic flame retardant, the acid absorber, the lubricant and the antioxidant are extruded from a twin-screw extruder, and after cooling, drying and pelletizing, a high oxygen index and low acid precipitation red phosphorus flame retardant polyamide composite is obtained; The polyamide resin, synergistic flame retardant, acid absorbent, lubricant and antioxidant are uniformly stirred and added from the No. 1 discharge port of the twin-screw extruder; the filling component is added from the No. 2 discharge port of the twin-screw extruder; the coated red phosphorus flame retardant masterbatch is added from the No. 3 discharge port of the twin-screw extruder; The process temperatures of the twin-screw extruder from the first feeding section to the die are: 240℃-280℃, 250℃-290℃, 250℃-290℃, 240℃-290℃, 230℃-280℃, 220℃-280℃, 210℃-270℃, 200℃-270℃, 200℃-270℃, 230℃-290℃.
Citation Information
Patent Citations
High glow-wire ignition temperature halogen-free flame-retardant reinforced nylon composite and preparation method thereof
CN103602061A
A bus interior trimming material having a high oxygen index and a low smoke density and a preparing method thereof
CN108997742A
Low-acid-separation red phosphorus inflaming retarding reinforced polyamide material as well as preparation method and application thereof
CN102382460A
High-toughness and precipitation-resistant red phosphorus flame-retardant nylon composite material and preparation method thereof
CN117659695A
Cited By
Low-smoke halogen-free flame-retardant cable for subway and preparation method thereof
CN120126876A
Low-halogen compound flame retardant for dripping non-combustible cotton and preparation method of low-halogen compound flame retardant
CN122188237A